PENGARUH SANDWICH LAMINATED COCO MAT DAN CHOPPED STRAND MAT TERHADAP KEKUATAN MATERIAL KOMPOSIT - -, Tarkono (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2009)
The application of coco fibre is widely open. In rural area, as a main source of coco fibre, the fibre IS only used for cooking and family products. As the technology development, how coco fibre can be applied as a part of composites materials. If it compound with other specific components, we can produce a new material with better mechanical properties. In this research, coco fibre with 0,2% wetness, compound with latex then pressed to get a coco mat with 2 mm thickness. Coco mat then formed with chopped strand mat to get a sandwich laminate composite. The original tensile strength of coco mat is 2,47 kgf/mm2 , and it will increased to 12,93 kgf/mm2 if it formed as sandwich laminate coco fibre. The tensile strength improves about 80, 90%.